The "Green Mile": crystallization ethnography in an emotive context. Issue 1 (14th April 2014) - C. Tallberg, Linda; J. Jordan, Peter; Boyle, Maree
Abstract : Purpose –: The purpose of this paper is to discuss emotions within a highly emotive organizational setting through the use of crystallization. The authors contend that the expression of a researcher's positionality as a presence within their research is crucial in contexts where conventional research approaches are unable to capture the depth of the phenomenon under study. The paper argues that the presentation of research findings from highly emotional organizational context will benefit from a challenge to traditional ways of representing and communicating the researcher's experience. As an example of this, in this paper the authors examine the emotions involved in experiencing animal euthanasia in a work context. Design/methodology/approach: – The paper draws ethnographic methods of fieldwork in an Australian animal shelter. The paper uses autoethnography and interview data. Findings: – Euthanasia is one of the most tolling experiences for animal shelter workers. This paper reveals that through a creative representation this experience may come induce understanding of the emotive context. Furthermore, the employees adapt one or more story-lines to deal with the conflict of euthanasia. Originality/value: – The strength of this paper is that it uses a novel approach to present findings in the form of crystallization. It also furthers insight on how organizational members explain their involvement in emotive work-tasks.